Electrically tunable fluidic lens imaging system for laparoscopic fluorescence-guided surgery - Volpi, Davide; Tullis, Iain D C; Barber, Paul R; Augustyniak, Edyta M; Smart, Sean C; Vallis, Katherine A; Vojnovic, Borivoj (Biomedical optics express, 2017)
The addition of fluorescence guidance in laparoscopic procedures has gained significant interest in recent years, particularly through the use of near infrared (NIR) markers. In this work we present a novel laparoscope camera coupler based on an electrically tunable fluidic lens that permits programmable focus control and has desirable achromatic performance from the visible to the NIR. Its use extends the lower working distance limit and improves detection sensitivity, important for work with molecularly targeted fluorescence markers. We demonstrate its superior optical performance in laparoscopic fluorescence-guided surgery. results using a tumor specific molecular probe and a nonspecific NIR dye are presented.